1992
DOI: 10.1002/bjs.1800790111
|View full text |Cite
|
Sign up to set email alerts
|

Temporary loop ileostomy following restorative proctocolectomy

Abstract: A retrospective study compared the outcome of restorative proctocolectomy in patients who had a covering ileostomy (n = 53) with those who had no proximal stoma (n = 32). Those who had a loop ileostomy had a higher incidence of anastomotic leakage (21 per cent), pelvic abscess (32 per cent) and postoperative fistula (28 per cent) than those with no covering ileostomy (6, 12 and 12 per cent respectively). Intestinal obstruction occurred in 23 per cent of those with an ileostomy, compared with 6 per cent in thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0
1

Year Published

1992
1992
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 5 publications
1
9
0
1
Order By: Relevance
“…32 Such risks are eliminated if a stoma is successfully omitted. The present study supports the findings of others who reported an increase in obstructive complications among patients receiving a stoma, 7,33,34 an effect that some authors have attributed to internal herniation around the stoma itself or to adhesions around the stoma site. 28 The results presented herein also showed a reduction in anastomotic stricture rate following stoma omission, presumably due to the pouch being used in the immediate postoperative period.…”
Section: Commentsupporting
confidence: 92%
“…32 Such risks are eliminated if a stoma is successfully omitted. The present study supports the findings of others who reported an increase in obstructive complications among patients receiving a stoma, 7,33,34 an effect that some authors have attributed to internal herniation around the stoma itself or to adhesions around the stoma site. 28 The results presented herein also showed a reduction in anastomotic stricture rate following stoma omission, presumably due to the pouch being used in the immediate postoperative period.…”
Section: Commentsupporting
confidence: 92%
“…Loop ileostomy has been shown to be associated with a higher incidence of intestinal obstruction in patients after restorative proctocolectomy [23,24]. The presence of an ileostomy has also been reported to be a significant risk factor for early SBO in a report by MacLean et al on SBO following IPAA [14].…”
Section: Discussionmentioning
confidence: 95%
“…[3][4][5][6][7][8][9][10][11] In addition, some authors have reported a higher morbidity after ileostomy closure associated with restorative proctocolectomy than that associated with low colorectal or coloanal anastomoses. [3][4][5][6][7][8] As a result, a selective approach to the use of a defunctioning loop ileostomy after restorative proctocolectomy has been advocated.…”
Section: Discussionmentioning
confidence: 99%
“…However, reports of high complication rates of ileostomy closure after restorative proctocolectomy have discouraged the routine use of a defunctioning ileostomy. [3][4][5][6][7][8] Furthermore, there is concern about the need for a second operation with time in the hospital and off work.…”
mentioning
confidence: 99%